Uma contribuição para a avaliação do número de octano de misturas de hidrocarbonetos - Santos, Dinarte (2018)
A new methodology for estimating the octane number of commercial gasolines and intermediate oil refinery streams is presented in this work. Chemical composition as well as physicochemical properties and octane numbers of the constituent hydrocarbons are taken as input parameters in this calculation. The proposed methodology was developed considering a simplified mechanism of the hydrocarbon pre-oxidation kinetics, which allows evaluating the production rate of hydrogen peroxide in the combustion chamber of the engine used in standard octane number evaluation tests (CFR engine). Furthermore, a thermodynamic two-zone model was used to describe the combustion process that takes place in this engine. This methodology was used to estimate the octane number of hydrocarbon blends containing linear paraffins, branched paraffins, aromatic, oleffinic and cycloparafinic components. These estimatedvalues were compared with experimental data and it was found that the mean quadratic deviation was 0.54 octane units in the case of paraffinic blends, and 1,0 in the case of paraffinic and aromatic blends.